2013
DOI: 10.4238/2013.march.11.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between Lolium (Poaceae) species revealed by RAPD markers

Abstract: ABSTRACT. The genus Lolium is one of the most important groupings of temperate forage grasses, including about eight recognized species that are native to some temperate and subtropical regions of the northern hemisphere. We examined genetic relationships among 18 accessions representing all Lolium species using RAPD markers. Among 50 random primers that we screened, 13 gave reproducible amplification banding patterns. Each of these 13 primers generated 19-43 scorable fragments. A total of 367 RAPD fragments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Also, analogous results have already been described via isozyme [40], morphological analysis, and electrophoresis of seed proteins [53,54]. Nevertheless, according to RAPD [55,56] or AFLP data [57], L. multiflorum has a position closer to that of L. perenne than to that of L. rigidum. Several factors might explain the above controversy, such as different clustering methods, characteristics of genetic markers, sample size, and number of studied species.…”
Section: Discussionsupporting
confidence: 66%
“…Also, analogous results have already been described via isozyme [40], morphological analysis, and electrophoresis of seed proteins [53,54]. Nevertheless, according to RAPD [55,56] or AFLP data [57], L. multiflorum has a position closer to that of L. perenne than to that of L. rigidum. Several factors might explain the above controversy, such as different clustering methods, characteristics of genetic markers, sample size, and number of studied species.…”
Section: Discussionsupporting
confidence: 66%
“…However, there is little information about the genetic diversity of Lolium (Guthridge et al, 2001). Previous studies have used random amplification of polymorphic DNA (Ma et al, 2013), while SRAP was used to identify the parent generation.…”
Section: Introductionmentioning
confidence: 99%
“…There is no morphological difference between the annual L. rigidum and L. loliaceum, as they are similar in the asymmetric karyotype. According to the information from the scatter graph, it is thought that the genotypes in the groups 1 and 2 may be related to L. rigidum, L. multiflorum and L. perenne when the karyotype formula and chromosome asymmetry are considered (Ma et al 2013). In general, studies have shown that those with primitive type karyotypes are associated with L. rigidum and those with types of anthropometric symmetric chromosomes are associated with L. perenne or perennial L multiflorum.…”
Section: Resultsmentioning
confidence: 99%